ANALISIS HUBUNGAN KEMAMPUAN KOMUNIKASI MATEMATIS DAN MINAT BELAJAR SISWA SMP DENGAN MENGGUNAKAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION - Marzan Armania; Siti Eftafiyana; Asep Ikin Sugandi (IKIP Siliwangi, 2018)
Abstract This study aimed to analyze the correlation between Mathematical Communication skill and learning interest of Junior High School students by using The Realistic Mathematic Education (RME) approach. The method used in study is using the Quasi-experimental method, by picking up two different (2) classes occupied by Junior High Students in Bandung Residence, and there will be two (2) classestaken as the sample of this study. the first class (experimental)use the Realistic Mathematics Education (RME) Approach, while the second class (Control) use the usual learning. The questionnaire answer then transformed by using the Method of Successive Interval (MSI), and the data will be tested by using the Product Moment Pearson and Spearmant Theory. The result of this study may point that there is a significant correlation between Mathematical Communication Skill and The Learner's Interest in Studying Mathematics. Keywords: Mathematical Communication, Learning Interests, Realistic Mathematic Education Approach.